Efficient image processing and machine learning approach for predicting retinal diseases - Hasib, Mehadi Hasan; Sultana, Tasnim; Chowdhury, Chandrika (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.